How melanism affects the sensitivity of lizards to climate change. (9th January 2022) - Mader, Sebastian; Goldenberg, Jonathan; Massetti, Federico; Bisschop, Karen; D'Alba, Liliana; Etienne, Rampal S.; Clusella‐Trullas, Susana; Shawkey, Matthew D.
Abstract: The impact of climate change on global biodiversity is firmly established, but the differential effect of climate change on populations within the same species is rarely considered. In ectotherms, melanism (i.e. darker integument due to heavier deposition of melanin) can significantly influence thermoregulation, as dark individuals generally heat more and faster than bright ones. Therefore, darker ectotherms might be more susceptible to climate change. Using the colour‐polyphenic lizard Karusasaurus polyzonus (Squamata: Cordylidae), we hypothesized that, under future climatic projections, darker populations will decrease their activity time more than brighter ones due to their greater potential for overheating. To test this, we mechanistically modelled the body temperatures of 56 individuals from five differently coloured populations under present and future climate conditions. We first measured morphological traits and integumentary reflectance from live animals, and then collected physiological data from the literature. We used a biophysical model to compute activity time of individual lizards as proxy for their viability, and thereby predict how different populations will cope with future climate conditions. Contrary to our expectations, we found that all populations will increase activity time and, specifically, that darker populations will become relatively more active than bright ones. This suggests that darker populations of K. polyzonus may benefit from global warming. Our study emphasizes the importance of accounting for variation between populations when studying responses to climate change, as we must consider these variations to develop efficient and specific conservation strategies. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.